Salt marsh-atmosphere CO2 exchanges in Patos Lagoon Estuary, Southern Brazil - Souza, Ronald B.; Copertino, Margareth S.; Fisch, Gilberto; Santini, Marcelo F.; Pinaya, Walter H. D.; Furlan, Fabiane M.; Alves, Rita de Cássia M.; Möller, Osmar O.; Pezzi, Luciano P. (Frontiers in Marine Science, 2022)
Blue carbon ecosystems are recognized as carbon sinks and therefore for their potential for climate mitigation. While carbon stocks and burial rates have been quantified and estimated regionally and globally, there are still many knowledge gaps on carbon fluxes exchanged particularly at the interface vegetation-atmosphere. In this study we measured the atmospheric CO2 concentrations in a salt marsh located in the Patos Lagoon Estuary, southern Brazil. Eddy correlation techniques were applied to account for the CO2 exchange fluxes between the vegetation and the atmosphere. Our dataset refers to two sampling periods spanning from July up to November 2016 and from January to April 2017. By using time series analysis techniques including wavelet and cross-wavelet analysis, our results show the natural cycles of the CO2 exchanges variability and the relationship of these cycles with other environmental variables. We also present the amplitudes of the salt marsh-atmosphere CO2 fluxes’ diurnal cycle for both study periods and demonstrate that the CO2 fluxes are modulated by the passage of transient atmospheric systems and by the level variation of surrounding waters. During daytime, our site was as a CO2 sink. Fluxes were measured as -6.71 ± 5.55 μmol m-2 s-1 and -7.95 ± 6.44 μmol m-2 s-1 for the winter-spring and summer-fall periods, respectively. During nighttime, the CO2 fluxes were reversed and our site behaved as a CO2 source. Beside the seasonal changes in sunlight and air temperature, differences between the two periods were marked by the level of marsh inundation, winds and plant biomass (higher in summer). The net CO2 balance showed the predominance of the photosynthetic activity over community respiration, indicating the role of the salt marsh as a CO2 sink. When considering the yearly-averaged net fluxes integrated to the whole area of the Patos Lagoon Estuary marshes, the total CO2 sink was estimated as -87.6 Mg C yr-1. This paper is the first to measure and study the vegetation-atmosphere CO2 fluxes of a salt marsh environment of Brazil. The results will contribute to the knowledge on the global carbon budget and for marsh conservation and management plans, including climate change policies.